A Study on IOGP Life-Saving Rules Among Workers in the Oil and Gas Industry - Mohd Rizal, Fatin Qaisara; Sahak, Nurrul Hafeezah; Ab Rahim, Hazrizal (Progress in Engineering Application and Technology, 2024)
This study evaluates the effectiveness of the International Association of Oil & Gas Producers (IOGP) Life-Saving Rules in ensuring worker safety within the oil and gas industry. These rules target high-risk activities and common workplace hazards, which are major causes of incidents and high-potential (HiPo) events. Primary data was collected through a questionnaire survey distributed to 524 oil and gas personnel, with a sample size of 217 determined using the Krejcie and Morgan Table. Secondary data included statistical incident reports and Unsafe Condition and Unsafe Act (UCUA) submissions. Findings reveal high individual knowledge scores but variable overall awareness, indicating a need for consistent education and training. The Level of Practice had a mean score of 2.97 (SD = 0.53), suggesting strong adherence to the rules. The study concludes that while overall knowledge about Life-Saving Rules is high, factors such as inconsistent communication and lack of a unified safety culture hinder optimal practice. Key recommendations for improvement include enhancing communication through various channels, continuous safety education through induction programs and toolbox talks, and frequent audits to ensure compliance and proactively address safety concerns. By addressing these factors, the study aims to enhance safety protocols, improve worker well-being, and strengthen organizational reputation within the oil and gas sector.